2016
DOI: 10.1073/pnas.1612369114
|View full text |Cite
|
Sign up to set email alerts
|

Edge effects enhance carbon uptake and its vulnerability to climate change in temperate broadleaf forests

Abstract: Forest fragmentation is a ubiquitous, ongoing global phenomenon with profound impacts on the growing conditions of the world's remaining forest. The temperate broadleaf forest makes a large contribution to the global terrestrial carbon sink but is also the most heavily fragmented forest biome in the world. We use field measurements and geospatial analyses to characterize carbon dynamics in temperate broadleaf forest fragments. We show that forest growth and biomass increase by 89 ± 17% and 64 ± 12%, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
105
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(117 citation statements)
references
References 33 publications
8
105
4
Order By: Relevance
“…In the broadleaf forests of Quebec, Canada, no changes in aboveground C stocks were observed within 100 m of an edge, although stem density increased (Ziter et al . ); in contrast, in broadleaf forests of eastern Massachusetts, Reinmann and Hutyra () found a 64% increase in forest biomass within 20 m of an edge. Similarly, in montane temperate lodgepole pine ( Pinus contorta ) forests in British Columbia, Canada, biomass was 31% higher in edges adjacent to roads than in the forest interior (Bowering et al .…”
Section: The Terrestrial C Cyclementioning
confidence: 94%
See 3 more Smart Citations
“…In the broadleaf forests of Quebec, Canada, no changes in aboveground C stocks were observed within 100 m of an edge, although stem density increased (Ziter et al . ); in contrast, in broadleaf forests of eastern Massachusetts, Reinmann and Hutyra () found a 64% increase in forest biomass within 20 m of an edge. Similarly, in montane temperate lodgepole pine ( Pinus contorta ) forests in British Columbia, Canada, biomass was 31% higher in edges adjacent to roads than in the forest interior (Bowering et al .…”
Section: The Terrestrial C Cyclementioning
confidence: 94%
“…Quantifying changes in C sequestration at the forest scale requires an inventory of all trees, given that increases in biomass with proximity to the edge could be attained (1) through faster‐growing individual trees at the edge or (2) through a higher density of trees at the edge, with the growth rates of each tree equal to the growth rates of trees within the forest interior. To our knowledge, the only study that has examined forest growth rates in an edge‐to‐interior context found evidence for both of these mechanistic pathways, leading to an 89% increase in forest growth within 20 m of a forest edge relative to the forest interior (Reinmann and Hutyra ). Furthermore, enhancement of temperate forest edge growth was greatest in years with cool summers and lowest in years with warmer than average summers, with absolute rates of forest growth declining nearly three times faster at the edge than in the interior in response to early growing season heat stress (Reinmann and Hutyra ).…”
Section: The Terrestrial C Cyclementioning
confidence: 99%
See 2 more Smart Citations
“…Changes in climate and natural and human induced disturbances are becoming more frequent and severe (IPCC, 2014), demanding more predictive power about how changes in ecosystem structure and function will alter resilience to disturbances. Future policy, conservation or restoration applications depend on reliable theories such as the theory of MEP presented here, to maintain ecosystem services and 20 ecological function (Haddeland et al, 2014;Porter et al, 2012;Reinmann and Hutyra, 2016;Thom et al, 2017). This is especially critical for anthropogenically modified systems, as their land use history can affect changes in energy use efficiency and thus alter their ability to recover from disturbances (Bürgi et al, 2016;Foster et al, 2003).…”
Section: Discussionmentioning
confidence: 99%